Penerapan Routing EIGRP, RIPv2 Dan OSPF Pada IPv6 Menggunakan Metode Redistribution - Maulana, Andry; Harafani, Hani; Setiawan, Ade (Universitas Pendidikan Ganesha, 2018)
The benefits of a computer network are to be able to exchange information and facilitate the work. Information sent from one network to another cannot be separated from the use of the router. Determination of network address can be done by routing method. Routing on many routers is easier and more efficient when using dynamic routing like EIGRP, OSPF,Â and RIP. Different route settings become a problem in data transmission. The purpose of this study is to explain the method of routing data transmission route routing. The routing redistribution method is chosen as one way to connect the routing method by combining the method using IPv6. Based on the results of the tests conducted on redistribution routing by looking at the length of time the data packet delivery with ICMP then obtained EIGRP redistribution routing to OSPF with an average value of 3.478 seconds and OSPF redistribution to RIP with an average of 3.486 seconds, and EIGRP redistribution to RIP with average 3,514 seconds. While the value of ICMP data transmission the longest by using OSPF redistribution to EIGRP with an average of 4.976 seconds, RIP redistribution to EIGRP with an average of 4.616 seconds and RIP redistribution to OSPF with an average of 4.462 seconds.